Identification of Acoustic Wave Orientation for Ultrasound-Based Flow Measurement by Exploiting the Hough Transform - Ploß, Peter; Rupitsch, Stefan; Fröhlich, T.; Lerch, Reinhard (Elsevier BV, 2012)
Ultrasound-based flow measurement relies on the proper knowledge of the angle under which the acoustic waves propagate with respect to the flow direction of the streaming fluid. We present a novel image processing approach for the identification of the wavefronts' orientation by exploiting a modified Hough transform. The spatially discretized sound pressure amplitude of measurement/simulation data is utilized as a weighting function for the Hough transform. It is shown that the angle and position of a wavefront can be estimated with subpixel accuracy, where the size of a pixel depends on the data's spatial resolution. This is achieved by incorporating a least-squares algorithm, fitting a 2D Gaussian function to the Hough parameter plane and thus improving the accuracy of the detected wavefront properties. (C) 2012 Elsevier Ltd....Selection and/or peer-review under responsibility of the Symposium Cracoviense Sp. z.o.o.
Keywords: flow measurement; ultrasound; wavefront orientation; Hough transform; image processing; subpixel accuracy